Sosialisasi Kajian Studi Kelayakan Bisnis Untuk Memulai Usaha Bagi Masyarakat Desa Mela II, Mecamatan Tapian Nauli, Kabupaten Tapanuli Tengah - Hasibuan, Nur’ainun; Fitryany Daulay , Fitryany; Nelly Azwarni Sinaga , Nelly Azwarni; Nova Zulfani Panggabean , Nova Zulfani; Tiurlina Hasmawati Sihite, Tiurlina Hasmawati (Cattleya Darmaya Fortuna, 2025)
The purpose of this Community Partnership Service (PKM) program is to provide the residents of Mela II Village with an understanding of the key aspects of a business feasibility study that should be considered before starting a business. This training also aims to increase the community's income through beach tourism businesses, so that the tourism sector in Mela II Village, Central Tapanuli Regency, can develop like other beaches in the area. The implementation of the training consists of 3 stages: (1) Training Preparation Stage, (2) Training Implementation Stage, (3) Final Evaluation Stage. The PKM community service partner is the people of Mela II Village, Tapian Nauli District, Central Tapanuli Regency. The main issue of the partner is how to convey to the community that Mela II Village also has the potential to develop like other areas, as long as the entire community has the intention and purpose to grow. In addition, the people of Mela II Village, Tapian Nauli District, Central Tapanuli Regency, are expected to further understand business opportunities by utilizing regional potential with limited capital, but which can provide substantial profits. It is anticipated that this program will proceed effectively, leading to an increase in the community's knowledge.